KERAGAMAN KARAKTER KUANTITATIF PADA TIGA GALUR HARAPAN MENTIMUN (Cucumis sativus L.) DI DATARAN MENENGAH - Mardiana, Yushi; Ervan Parayan (JURNAL AGROTROPIKA, 2025)
Breeding lines in crop improvement represent selected genotypes with potential to be developed into superior cultivars. This study aimed to evaluate the genetic variability, adaptability, and yield stability of promising cucumber lines under mid-altitude conditions. The experiment was conducted from December 2024 to February 2025 at the PT. Aditya Sentana Agro experimental farm, Girimoyo Village, Malang, East Java, at an altitude of 525 m above sea level. A randomized complete block design (RCBD) was applied with three cucumber breeding lines and four commercial check varieties, namely New Oris F1, Renata F1, Madavi F1, and Zatavy F1. Each treatment was replicated four times with six plants per plot. Data were analyzed using ANOVA, followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level when significant differences were detected. The results revealed significant variation in several traits, including days to flowering, fruit length, fruit weight per plant, and yield, while no significant variation was observed in harvesting time, fruit diameter, fruit weight per fruit, and number of fruits per plant. The earliest flowering was observed in Line C (26.25 DAS), although it was later than the check variety Madavi (25.26 DAS). The longest fruit length was obtained from Line A (23.05 cm), surpassing both other lines and check varieties. Line A also produced the highest fruit weight per plant (1354.42 g), yet it remained lower than Zatavy (1421.92 g). Similarly, the highest yield was recorded in Line A (31.31 t ha⁻¹), although still below Zatavy (32.87 t ha⁻¹).